Strategi Komunikasi Krisis Humas PTMB dalam Mengelola Gangguan Layanan Air Perkotaan: Perspektif Situational Crisis Communication Theory - Camelia Ananda Arifin; Silviana Purwanti; Kadek Dristiana Dwivayani (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
Water supply disruptions in Balikpapan have evolved beyond technical service failures into a public communication challenge affecting organizational credibility. This study aims to analyze the crisis communication strategies employed by the Public Relations division of Perumda Tirta Manuntung Balikpapan (PTMB) in responding to water-related crises using the Situational Crisis Communication Theory (SCCT). A qualitative case study approach was employed, with data collected through in-depth interviews, observations, and document analysis involving PTMB public relations personnel and service users. Data were analyzed using the Miles and Huberman interactive model and validated through source triangulation. The findings indicate that PTMB primarily implemented the Diminish Strategy through excuse and justification to explain the causes of water disruptions and distribution constraints. The organization also adopted Rebuild Strategy through apology and compensation and Bolstering Strategy through ingratiation, reminding, and victimage to reinforce stakeholder trust. No evidence of Denial Strategy was identified. Overall, PTMB's crisis communication emphasized reducing organizational responsibility attribution while maintaining public confidence. Nevertheless, challenges remain regarding response timeliness and consistency of information dissemination. The study highlights the importance of adaptive crisis communication in strengthening public trust within essential public service organizations.